OPTIMALISASI TATA LETAK WORKSHOP FABRIKASI DENGAN METODE ARC DI PT XYZ - Sulistyo, Arif Budi; Nurul Ikhsan, Hadid (Inaque : Journal of Industrial and Quality Engineering, 2024)
This study aims to optimize the facility layout at PT. XYZ's Fabrication Workshop using the Activity Relationship Chart (ARC) method. The current facility layout causes operational inefficiencies, primarily due to excessive material handling distances. The research method involved collecting data on inter-area relationships and facility usage frequency, which were then processed using the ARC method and Blocplan software to generate several proposed layout iterations. Two selected layout proposals were further analyzed: the first layout with an adjacent score of 0.71 reduced material handling distance from 768.6 meters to 473.4 meters (a reduction of 38.4%), while the second layout with an adjacent score of 0.68 reduced the distance to 510 meters (a reduction of 33.6%). The study results indicate that the application of the ARC method is effective in improving the efficiency and effectiveness of the facility layout in the workshop and enhancing the working environment conditions.